IMPACTS OF THE PANDEMIC ON AGRICULTURAL PESTICIDE PRICES - de Araujo, Gabriel Pinelli; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2022)
The COVID-19 pandemic certainly represents the greatest global public health crisis since the 1918 influenza outbreak, due to its high transmission capacity and worsening of the health status of an infected person. In a matter of months, the pandemic affected virtually every country in the world, which not only impacts the health of the population, but affects all areas of life in society, such as physical and mental health, the economy, and public accounts, as well as the input production and distribution chains. This means that the transport, education, finance and manufacturing sectors are severely affected by measures aimed at controlling the health emergency. Given this scenario, it has become a habit for some families to buy large volumes of groceries at once in order to face the days of social isolation, thus generating problems for the turnover of stocks. This study aims to explore the impacts of the pandemic on agriculture with repercussions on logistics and prices of agricultural defensives, which will be based on a literature review on the subject based on qualitative bibliographical research and exploratory intent. At the end of this literature review, it was possible to verify that several different phenomena and from different origins converge to impact the prices of agricultural inputs, among them pesticides, and by extension the economic sustainability of agricultural enterprises.